Characteristics of dual carbapenemase-producing Klebsiella pneumoniae strains from an outbreak in Venezuela: a retrospective study - Dianny Martínez; Luisa Caña; Hectorina Rodulfo; José García; Diorelis González; Lucy Rodríguez; Marcos De Donato (Revista Panamericana de Salud Pública, 2020)
Objective. To characterize carbapenemase-producing Klebsiella pneumoniae isolated from patients treated at a hospital in Cumaná, Sucre, Venezuela. Methods. This was a retrospective study conducted at the general hospital in Cumaná where 58 K. pneumoniae strains were analyzed for resistance to antimicrobials, specifically carbapenems, in January – June 2015. Production of metallo-β-lactamases and serine carbapenemases was determined by the double-disc synergy test, using EDTA-sodium mercaptoacetic acid and 3-aminophenyl boronic acid discs, respectively. Multiplex-PCR was used to detect genes coding for carbapenemases. Molecular typing using ERIC-PCR determined the presence of clones. Results. Four strains of K. pneumoniae resistant to carbapenems were identified. Phenotypic methods for detection of metallo-β-lactamases and serine carbapenemases were positive, and PCR demonstrated the co-presence of blaNDM and blaKPC genes in all four strains. ERIC-PCR identified two clones circulating in the hospital. Conclusions. Infection control strategies are needed at the central hospital in Cumaná and its surrounding areas to prevent the spread of these pathogens, especially given the high levels of migration from Venezuela to other countries in South America.